Oxford photo dictionary: Practice exercises for classroom use or self-study (Oxford, 1999)
The book presents over 2.400 words (both Britisch and American English) in lively, colour photographs, covering the family, the human body and clothes, the home and the city, shops and food, the post office, money and the bank. school and work, science and the environment, travel, sport and animals.
Keywords: english language - study and teaching ( elementary ) - foreign speakers,language arts ( elementary )